Serum IgA antibodies against Pseudomonas aeruginosa in cystic fibrosis. Issue 3 (March 1990) - Brett, M M; Ghoneim, A T; Littlewood, J M
Abstract : Serum IgA antibodies to Pseudomonas aeruginosa cell surface antigens were estimated by ELISA. Titres in patients with and without cystic fibrosis and with no pseudomonal infection were low (less than 105 to less than 261). Titres in patients with cystic fibrosis who were chronically infected with P aeruginosa were very high (1200-163, 000), and patients who grew the organism intermittently had intermediate titres. Longitudinal studies suggested increasing tissue invasion or involvement of the lower respiratory tract, or both, with increasing time of infection and identified patients with a good prognosis after the onset of pseudomonal infection. Detection of an increased serum IgA titre can give an earlier indication than measurement of the serum IgG titre of the presence of P aeruginosa in the respiratory tract in a proportion of patients. IgA measurement seems to be better than IgG measurement at predicting the reappearance of P aeruginosa after apparent eradication of early infection. These results suggest that this assay may be a valuable additional indicator of the presence of P aeruginosa at the beginning of infection, and of the reappearance of the organism after treatment in the early stages of infection.